THE PREVALENCE OF PROBLEMATIC INTERNET USE AMONG NURSING STUDENTS: A DESCRIPTIVE SURVEY APPROACH (Journal of Pharmaceutical Negative Results, 2022)
BACKGROUND OF STUDY: Life with internet has become as easy as it keeps us updated about various information. The Internet has become an integral part of student’s life. Student nurses at the beginning of their career are so enthusiastic and curious about learning new things. They prefer browsing the internet about various procedures rather than asking professors. It is not only an integral part, but also has become a vital necessity in the daily life of people, especially students. Nevertheless, its use is also posing a threat to our belief, tending to lose the inner voice: weakening us from doing things to our fullest, which lies within our potential yet escaping to do so. It has important clinical implications, because it may be a common behavioral marker of significant mental health problems that might go understood.Aim: The aim of the study was to assess the prevalence of Problematic Internet Use among nursing students and to find out the association between Problematic Internet Use with selected socio-demographic variables.METHODS: A quantitative research approach with exploratory survey design was used to collect the data among 100 students of selected college of Vadodara. They were selected by the non-probability purposive sampling technique. Structured questionnaire was used to assess the prevalence of problematic Internet use. The collected data was analyzed and interpreted using SPSS version 25.RESULTS: The prevalence of problematic internet use among nursing students revealed that majority (58%) had moderate problematic followed by 38% had mild problematic and only 4% had no problematic internet use with median score of 62 and mean knowledge score was 59.98 with standard deviation was 15.23. The association between prevalence of problematic internet use among nursing students with their selected socio-demographic variables showed that gender of nursing students was statistically significant at p<0.05 level with prevalence of problematic internet use.